Idiopathic cutaneous T‐cell pseudolymphoma with prominent granulomatous reaction. Issue 1 (28th December 2019) - Iwai, Yuki; Ibusuki, Atsuko; Kawai, Kazuhiro
Abstract : Granulomatous components can be observed in cutaneous pseudolymphoma, but prominent granulomatous reaction may pose a potential diagnostic pitfall. We report a case of idiopathic cutaneous T‐cell pseudolymphoma with prominent granulomatous reaction.